Pelayanan Penerbitan Sertifikat Kepemilikan Tanah (Studi pada Kantor Pertanahan Nasional Kabupaten Bondowoso) - Wardaty, Sela Febby; Sumartono, Sumartono; Setyowati, Endah (Jurnal Ilmiah Administrasi Publik, 2020)
In the case of the development of public services, it is not merely an administrative problem or merely fulfilling the physical needs of service quality and customer satisfaction, especially considering that both of them have a major influence on the sustainability and development of an organization's mission. Such services must be accessible to the community without exception, regardless of socioeconomic status, race, ethnicity, religion and other subjective characteristics. As a service provider for citizens, the government is required to further optimize and be able and able to fulfill all its responsibilities to the community, both in terms of quality and quantity of service. Problems that occur in the Bondowoso District National Land Office are problems of poor service quality, good service quality will produce good output for the community and for the Land Office itself. The services available at the Land Office are a bit complicated and difficult for the public. The service of land certificates will make people's lives better with clear legal certainty.